Molecular insights into the interplay between type 2 diabetes mellitus and osteoporosis: implications for endocrine health - Jiang, Liyun; Song, Xia; Yan, Li; Liu, Yali; Qiao, Xiumei; Zhang, Wen (Frontiers in Endocrinology, 2025)
BackgroundType 2 diabetes mellitus (T2DM) and osteoporosis are prevalent, interconnected chronic diseases that significantly impact global health. Understanding their complex biological relationship is crucial for improving patient outcomes and treatment strategies.MethodThis review examines recent research on the mechanisms linking T2DM with osteoporosis. It focuses on how abnormalities in bone metabolism, autophagy, ferroptosis, and vitamin D receptor (VDR) gene polymorphisms contribute to osteoporosis in T2DM patients.ResultsOur analysis indicates that T2DM is associated with reduced bone formation and increased bone resorption, which are influenced by hormonal changes, inflammation, and disrupted cellular signaling pathways. Additionally, increased perirenal fat thickness worsens osteoporosis through local inflammation and altered adipokine levels. VDR gene polymorphisms provide new molecular insights into this connection.ConclusionAddressing the identified mechanisms with targeted management strategies may improve bone health in individuals with T2DM. Future research should explore these associations in greater detail to develop more effective prevention and treatment strategies.